Genetic Analysis of Ulcerative Colitis in Japanese Individuals Using Population-specific SNP Array. Issue 8 (19th February 2020) - Okamoto, Daisuke; Kawai, Yosuke; Kakuta, Yoichi; Naito, Takeo; Torisu, Takehiro; Hirano, Atsushi; Umeno, Junji; Fuyuno, Yuta; Li, Dalin; Nakano, Takeru; Izumiyama, Yasuhiro; Ichikawa, Ryo; et al.
Abstract: Background: To clarify the genetic background of ulcerative colitis (UC) in the Japanese population, we conducted a genome-wide association study (GWAS) using a population-specific single nucleotide polymorphism (SNP) array. Methods: We performed a GWAS and replication study including 1676 UC patients and 2381 healthy controls. The probability of colectomy was compared between genotypes of rs117506082, the top hit SNP at HLA loci, by the Kaplan-Meier method. We studied serum expression of miR-622, a newly identified candidate gene, from 32 UC patients and 8 healthy controls by quantitative reverse-transcription polymerase chain reaction. Results: In the GWAS, only the HLA loci showed genome-wide significant associations with UC (rs117506082, P = 6.69E-28). Seven nominally significant regions included 2 known loci, IL23R (rs76418789, P = 6.29E-7) and IRF8 (rs16940202, P = 1.03E-6), and 5 novel loci: MIR622 (rs9560575, P = 8.23E-7), 14q31 (rs117618617, P = 1.53E-6), KAT6B (rs12260609, P = 1.81E-6), PAX3-CCDC140-SGPP2 (rs7589797, P = 2.87E-6), and KCNA2 (rs118020656, P = 4.01E-6). Combined analysis revealed that IL23R p.G149R (rs76418789, P = 9.03E-11; odds ratio [OR], 0.51) had genome-wide significant association with UC. Patients with GG genotype of rs117506082 had a significantly lower probability of total colectomy than those with the GA+AA genotype ( P = 1.72E-2). Serum expression of miR-622 in patients with inactive UC tended to be higher than in healthy controls and patients with active UC (inactive UC vs healthy controls, P = 3.03E-02; inactive UC vs active UC, P = 6.44E-02). Conclusions: IL23R p.G149R is a susceptibility locus for UC in Japanese individuals. The GG genotype of rs117506082 at HLA loci may predict a better clinical course. Abstract : Genome-wide association study revealed that IL23R p.G149R is a susceptibility locus for UC in Japanese individuals. The GG genotype of rs117506082 at HLA loci may predict a better clinical course.